2014
DOI: 10.2807/1560-7917.es2014.19.25.20839
|View full text |Cite
|
Sign up to set email alerts
|

Two clustered cases of confirmed influenza A(H5N1) virus infection, Cambodia, 2011

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Despite one human-to-human transmission event in Thailand, available epidemiological data show that A(H5N1) transmission to those providing care is extremely rare [34, 35]. Furthermore, our detailed interviews showed that most study subjects who declared they provided care actually did little more than visit the human cases, without close or prolonged contact.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite one human-to-human transmission event in Thailand, available epidemiological data show that A(H5N1) transmission to those providing care is extremely rare [34, 35]. Furthermore, our detailed interviews showed that most study subjects who declared they provided care actually did little more than visit the human cases, without close or prolonged contact.…”
Section: Discussionmentioning
confidence: 88%
“…The identification of possible increased risks of A(H5N1) infection linked with hunting and consuming wild birds in Cambodia warrants further and careful study. Additional work is being conducted on documenting possible genetic polymorphisms associated with increased vulnerability or resistance to A(H5N1) infection in humans [34]. …”
Section: Resultsmentioning
confidence: 99%
“…Despite detection of human highly pathogenic avian influenza (HPAI) H5N1 virus in Western Cambodia since early 2011 [ 36 – 38 ], H5N1, typically detected in south-central Cambodia, was not found at our sentinel sites. Influenza subtypes varied by year with A/pH1N1(2009) being predominate in 2010, influenza B in 2011, and influenza A/H3N2 in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…There was also some minor loss to follow-up. Transmission risk estimates in villages with clusters might be influenced by the role of host genetics in susceptibility to infection ( 12 , 13 ). Our findings may therefore apply to genetically vulnerable persons and may have been overestimated, but they remain comparable to or lower than historical data in Cambodia.…”
Section: Discussionmentioning
confidence: 99%